2013
DOI: 10.1146/annurev-chembioeng-061312-103323
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradable Polyesters from Renewable Resources

Abstract: Environmental concerns have led to the development of biorenewable polymers with the ambition to utilize them at an industrial scale. Poly(lactic acid) and poly(hydroxyalkanoates) are semicrystalline, biorenewable polymers that have been identified as the most promising alternatives to conventional plastics. However, both are inherently susceptible to brittleness and degradation during thermal processing; we discuss several approaches to overcome these problems to create a balance between durability and biodeg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
50
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(52 citation statements)
references
References 158 publications
0
50
0
2
Order By: Relevance
“…It has been shown that these modifications result in PLA based materials with improved elongation at break, impact strength, toughness and barrier properties. However, similar to unmodified PLA, hydrolytic degradation remains a concern [12][13][14]. In fact depending on the hydrophilicity of the modifier used, the degradation rate of PLA has been found to increase in modified materials significantly affecting their processability [11,14].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that these modifications result in PLA based materials with improved elongation at break, impact strength, toughness and barrier properties. However, similar to unmodified PLA, hydrolytic degradation remains a concern [12][13][14]. In fact depending on the hydrophilicity of the modifier used, the degradation rate of PLA has been found to increase in modified materials significantly affecting their processability [11,14].…”
Section: Introductionmentioning
confidence: 99%
“…However, the brittle nature of PLA and other commercial aliphatic polyesters such as poly(butylene succinate) and poly (hydroxyalkanoate)s has thwarted their broad-based utility. Expanded market penetration will pivot on the development of products endowed with tunable combinations of properties, e.g., soft, ductile, and tough (17,18). Among myriad strategies that have been used to this end, PLA-containing block polymers represent a particularly attractive approach.…”
mentioning
confidence: 99%
“…A partir de monómeros derivados de recursos naturales y mediante síntesis química se pueden convertir en biomateriales [1,2,4,5,[34][35][36][37][38] como los poliésteres y el PLA. Un ejemplo es el enunciado por Dai y Qiu en 2016, en el que, por medio de una policondensación, en dos etapas, sintetizan materiales biodegradables: tres nuevos copoliésteres poli (succinato de butileno-co-succinato de decametileno) (PBDS) y su homopolímero poli (succinato de butileno) (PBS) a partir de monómeros biobasados como el ácido succínico, el 1,4-butanodiol y el 1,10-decanodiol [34].…”
Section: Polimerización De Bio-monómerosunclassified
“…Factores como nuevas posturas en sostenibilidad, avances en la nanotecnología y la crisis petrolera de las últimas décadas muestran una visión diferente en las tendencias para el aprovechamiento de los recursos naturales. Entre éstas, se encuentra una enfocada hacia la ciencia de los polímeros para desarrollar nuevos materiales a partir de recursos renovables en lugar de los tradicionales polímeros basados en fuentes fósiles que generan grandes cantidades de residuos no biodegradables y su disposición final se convierte en un grave problema [1][2][3][4][5], a pesar que existen programas de reciclaje [6][7][8]. Por ello, se hace necesario encontrar materiales preferentemente renovables, biodegradables e inofensivos para el medio ambiente.…”
Section: Introductionunclassified